PROGNOSTIC VALUE OF DIFFERENT OBESITY MARKERS FOR CARDIOVASCULAR RISK ASSESSMENT IN URBAN EMPLOYED MONGOLIANS - K. V. Protasov; T. Myagmarsuren (Российский кардиологический журнал, 2015)
We assessed the prevalence of obesity and identify obesity-related markers of elevated/high cardiovascular risk among urban employed Mongolians. 1277 railway workers aged 18-63 were investigated. Obesity parameters, blood pressure, lipids and fasting plasma glucose levels were measured. Body composition by bioelectrical impedance method was evaluated. 10-year risk for cardiovascular events was calculated. The results showed that the prevalence of general obesity was 65,4% in men and 68,5% in women. Abdominal obesity was found in 58,5% of men and 76.1% of women. By ROC-analysis we revealed the obesity-related markers with the best diagnostic accuracy for elevated/high cardiovascular risk assessed by the Systematic Coronary Risk Evaluation, Framingham Heart Study and Atherosclerotic Cardiovascular Disease risk algorithms. For men they were waist circumference waist-to-height ratio, for women — the body fat percentage. The optimal cut off values for these predictors and corresponding odds ratios for risk increase were determined.